Constraints Perceived in Adoption of Improved Practices of Small Scale Dairying: A Gender Analysis - Jyoti Yadav , Hema Tripathi and Anirudha Kumar, (Indian Journal of Extension Education, 2013)
The present study was carried out in mid western plain zone of Uttar Pradesh to identify the various constraints perceivedseparately by female and male headed households in adopting improved practices in small scale dairying. Data werecollected through interview schedule from 50 female and 50 male headed households. The study revealed that the majorconstraints among breeding practices perceived by females and male respondents were same i.e. non functioning of A.I.centre/ill equipped A.I. centre followed by scarcity of resources to maintain crossbred cattle/superior breed of milchanimals. Inadequate knowledge about scientific feeding, high cost of ingredients of concentrates mixture and preferenceto grow cash crops instead of fodder crops were found to be the first, second and third major constraints in both sets ofrespondents in adoption of improved feeding practices. Lack of knowledge about common contagious diseases, theircauses & control measures (Ist), ill equipped veterinary hospitals and lack of facility for treatment, vaccine (IInd) were theconstraints perceived by women respondents.